Strategi Balai Karantina Pertanian Tanjungpinang Dalam Meningkatkan Potensi Ekspor Karet Bintan - Sinta; Clara Eliza; Shalsiana Rusfatiha (Public Knowledge, 2025)
Of the many Indonesian export commodities in the plantation sector, one of the leading ones is natural rubber. This is based on the increasingly high world demand for natural rubber. Rubber is known for its elastic properties and is a raw material used in many products and equipment around the world, ranging from industrial products to household products. As is well known, Indonesia is the country with the largest rubber plantation area in the world. However, in terms of productivity, Indonesia is still below Thailand and Malaysia. This shows the inefficiency of rubber processing in Indonesia so far. Taking case in Bintan Regency, Kepuauan Riau Province, one of the areas that has rubber plantations for export, the purpose of this research and journal writing is to find out the extent of the development of efforts made by the Badan Karantina Pertanian Tanjungpinang in increasing the export of rubber from Bintan.